The Contribution of School-Based Teacher Professional Development to Learner-Centred Pedagogical Practices in Secondary Schools in Tanzania - Rugambwa, Allen; Anangisye, William A. L.; Mwaikokesya, Mpoki J. (Papers in Education and Development, 2022)
Abstract The study investigated how school-based teacher professional development (SB-TPD) contributes to learner-centred pedagogical (LCP) practices in secondary schools in Tanzania. The study employed a mixed-methods research approach and a convergent-parallel design in collecting and analysing data from a sample of 111 teachers participating in the Probono Teacher Training (PTT) Programme in Kilimanjaro and Dar es Salaam regions. The study revealed that the PTT Programme contributed to the improvement of the application of learner-centred teaching (LCT) techniques, improvisation of teaching aids, and laboratory management practices. It also contributed to the active participation of students in group discussions and laboratorybased experimental activities. It was, therefore, the conclusion of the study that SB-TPD contributes significantly to the improvement of LCP in secondary schools. Keywords: engagement in learning, learner-centred pedagogy, professional development